After the expulsion West Germany and Eastern Europe 1945-1990 - Ahonen, Pertti (Oxford University Press, 2003)
This text examines the long-term consequences of the largest 'ethnic cleansing' operation in 20th-century Europe - the removal of up to 15 million Germans from Central and Eastern Europe at the end of the Second World War.